In vitro degradation and metabolism of sulphur supplemented oat hay by anaerobic fungi from buffalo and cattle - DULAR, R K; SANGWAN, D C (The Indian Journal of Animal Sciences, 2014)
In vitro rumen simulated study was conducted by fermenting oat hay with anaerobic fungi from buffalo and cattle under dietary sulphur levels of 0. 1,0.2,0.3 and 0.4% (on DM basis) for various time intervals. Ruminal disappearances of dry matter, gas production, rumen metabolites and cellulase activity were influenced (P